Нормативне регулювання технічного захисту інформації в Україні - Шепєта, О.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Аргументируется позиция, что одним из действенных шагов на пути повышения эффективности данного регулирования является исследование и классификация системы нормативных актов, регулирующих ТЗИ в Украине, а также определения места и роли источников отдельных отраслей права в общей системе нормативного регулирования технической защиты информации в Украине. Growing up a threat rate for information caused a necessity to improve a law regulating of technical defense of information. Is argumented, that one of the effective step in this activity is research and classification of whole law acts, which regulates technical defense of information. Besides very constructive, according to author's view, is defining the place and role of some branch of law in general system of law regulating of technical defense of information.